Balanced complex chromosome rearrangement in male infertility: case report and literature review. (24th February 2014) - Nguyen, M. H.; Morel, F.; Pennamen, P.; Parent, P.; Douet‐Guilbert, N.; Le Bris, M. J.; Basinko, A.; Roche, S.; De Braekeleer, M.; Perrin, A.
Summary Complex chromosome rearrangements (CCRs) are structural rearrangements involving at least three chromosomes and three or more chromosome breakpoints. Generally, balanced CCR carriers have a normal phenotype but they are at a higher reproductive risk. Azoospermia was discovered in the male partner of a couple with primary infertility. Conventional cytogenetics identified a CCR refined by fluorescent in situ hybridisation. The CCR involved three chromosomes, four breakpoints and an insertion. A literature search identified 43 phenotypically normal males referred for reproductive problems presenting a CCR. More males were ascertained because of spermatogenesis failure or disturbances than because of repeated abortions and/or birth of a malformed child. Male carriers of CCR produce a high frequency of chromosomally abnormal spermatozoa due to the aberrant segregation of the rearranged chromosomes. The number of chromosomes and breakpoints involved in the rearrangement, the position of breakpoints, the relative size of the resultant chromosomes and the presence or absence of recombination inside the paired‐rearranged segments are presumed to affect the fertility of the carrier. Testicular biopsy should not be performed in males with azoospermia. Intracytoplasmic sperm injection should not be proposed as a procedure for treating the infertility of CCR male carriers as a successful result is unlikely.